Nonaqueous electrolyte secondary battery
By adding high-content carbon nanotubes to the positive electrode active material layer of the lithium-ion secondary battery and controlling the pore diameter, the problem of degradation of durability caused by too small pores of the positive electrode active material layer is solved, and high initial resistance and storage characteristics are achieved The improvement is suitable for power supply for electric vehicles and other vehicles.
Patent Information
- Application Number
- CN202410926241.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
In lithium-ion secondary batteries, the high density of the positive electrode active material layer causes the pore diameter to be too small, making it difficult to form a film uniformly, reducing the durability and storage characteristics of the non-aqueous electrolyte secondary battery, especially in the power supply for vehicle driving High initial resistance and storage characteristics are required.
By adding 0.2% to 1.0% by mass of carbon nanotubes as conductive material to the positive electrode active material layer, it is ensured that 80% by mass of the conductive material is carbon nanotubes, and the peak pore diameter of the positive electrode active material layer is controlled to be 0.50 μm ~0.70μm, the capillary phenomenon of conductive material is used to improve the impregnation of the nonaqueous electrolyte, so that the positive electrode film forming agent is uniformly spread to the pores, forming a good conductive path.
A nonaqueous electrolyte secondary battery with excellent initial resistance and storage characteristics despite the small pores of the positive electrode active material layer is realized, and the initial resistance and long-term storage capacity stability of the lithium-ion secondary battery is improved.
Smart Images

Figure CN119315032A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries have been used favorably as portable power sources for personal computers and portable terminals, and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).
[0003] The positive electrode used for non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries generally has a structure in which a positive electrode active material layer is provided on a positive electrode current collector. The positive electrode active material layer contains positive electrode active material particles, and the positive electrode active material layer has pores formed by the gaps between the positive electrode active material particles (for example, refer to patent documents 1 to 3). In order to improve the performance of non-aqueous electrolyte secondary batteries, it is known that a technology that contains an additive (also called a so-called "positive electrode film forming agent" or "positive electrode additive") that forms a film on the positive electrode is contained in the non-aqueous electrolyte (for example, refer to patent document 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-069822
[0007] Patent Document 2: International Publication No. 2021 / 186949
[0008] Patent Document 3: International Publication No. 2023 / 054308 Summary of the invention
[0009] At present, the demand for BEV is rapidly increasing, and further high performance of secondary batteries for driving power sources of BEV is desired. As one of the methods for high performance, a method of increasing the density of the positive electrode active material layer can be cited. The inventors of the present invention have conducted in-depth research and found that the following problems exist when the positive electrode active material layer is increased in density. That is, if the positive electrode active material layer is increased in density, the pore diameter of the positive electrode active material layer becomes excessively small, and it is difficult for the positive electrode film forming agent to penetrate into the fine parts of the pores of the positive electrode active material layer. As a result, it is difficult to form a film uniformly in the positive electrode active material layer, resulting in a decrease in the durability of the non-aqueous electrolyte secondary battery. Specifically, the capacity degradation of the non-aqueous electrolyte secondary battery during storage becomes larger. In addition, for the secondary battery used in the vehicle driving power source, a high initial resistance characteristic is required.
[0010] Therefore, an object of the present invention is to provide a nonaqueous electrolyte secondary battery having excellent initial resistance characteristics and storage characteristics despite having small pores in a positive electrode active material layer.
[0011] The nonaqueous electrolyte secondary battery disclosed herein contains a positive electrode, a negative electrode, and a nonaqueous electrolyte. The positive electrode includes a positive electrode collector and a positive electrode active material layer supported on the positive electrode collector. The positive electrode active material layer contains a positive electrode active material and a conductive material. The peak pore diameter of the positive electrode active material layer is 0.50 μm to 0.70 μm. The content of the conductive material in the positive electrode active material layer is 0.2 mass % to 1.0 mass %. More than 80 mass % of the conductive material is carbon nanotubes. The nonaqueous electrolyte contains a nonaqueous solvent, an electrolyte salt, and a positive electrode film forming agent.
[0012] According to such a configuration, it is possible to provide a nonaqueous electrolyte secondary battery having excellent initial resistance characteristics and storage characteristics despite having small pores in the positive electrode active material layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a cross-sectional view schematically showing the internal structure of a lithium ion secondary battery according to one embodiment of the present invention.
[0014] Figure 2 This is an exploded schematic diagram showing the structure of a wound electrode body of a lithium ion secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0015] The following describes the embodiments of the present invention with reference to the accompanying drawings. Furthermore, matters not mentioned in this specification, that is, matters required for the implementation of the present invention, can be understood as design matters for those skilled in the art based on the prior art in this field. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in this field. In addition, in the following drawings, the same figure marks are marked on the components and parts that play the same role for illustration. In addition, the dimensional relationships (length, width, thickness, etc.) in each figure do not reflect the actual dimensional relationships. It should be noted that A and B are included in the numerical range expressed as "A~B" in this specification.
[0016] It should be noted that in this specification, "secondary battery" refers to a storage device that can be repeatedly charged and discharged. In addition, in this specification, "lithium-ion secondary battery" refers to a secondary battery that uses lithium ions as charge carriers and uses the movement of charges accompanying lithium ions between positive and negative electrodes to achieve charging and discharging. Furthermore, the so-called "electric vehicle (BEV)" in this specification refers to a car that has a motor that uses a secondary battery as a power source, but does not have an internal combustion engine such as a gasoline engine.
[0017] The present invention is described in detail below by taking a flat rectangular lithium ion secondary battery having a flat wound electrode body and a flat battery case as an example, but the present invention is not intended to be limited to the technical solutions described in this embodiment.
[0018] Figure 1 The lithium-ion secondary battery 100 shown is a sealed battery constructed by accommodating a flat wound electrode body 20 and a non-aqueous electrolyte 80 in a flat square battery case (i.e., an outer packaging container) 30. The battery case 30 is provided with a positive terminal 42 and a negative terminal 44 for external connection, and a thin-walled safety valve 36 designed to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or more. In addition, the battery case 30 is provided with an injection port (not shown) for injecting the non-aqueous electrolyte 80. The positive terminal 42 is electrically connected to the positive electrode collector plate 42a. The negative terminal 44 is electrically connected to the negative electrode collector plate 44a. As the material of the battery case 30, for example, a metal material with a light weight and good thermal conductivity, such as aluminum, is used. Furthermore, Figure 1 The amount of the nonaqueous electrolyte 80 is not accurately indicated.
[0019] The wound electrode body 20 is Figure 1 and Figure 2 As shown, the positive electrode sheet 50 and the negative electrode sheet 60 are overlapped via two long strip separator sheets 70 and wound in the longitudinal direction. The positive electrode sheet 50 has a structure in which a positive electrode active material layer 54 is formed on one side or both sides (here both sides) of a long strip positive electrode collector 52 along the longitudinal direction. The negative electrode sheet 60 has a structure in which a negative electrode active material layer 64 is formed on one side or both sides (here both sides) of a long strip negative electrode collector 62 along the longitudinal direction. The positive electrode active material layer non-formed portion 52a (i.e., a portion where the positive electrode active material layer 54 is not formed and the positive electrode collector 52 is exposed) and the negative electrode active material layer non-formed portion 62a (i.e., a portion where the negative electrode active material layer 64 is not formed and the negative electrode collector 62 is exposed) are formed in a manner that they are exposed to the outside from both ends of the winding axis direction (i.e., the sheet width direction orthogonal to the above-mentioned longitudinal direction) of the wound electrode body 20. The positive electrode current collector plate 42a and the negative electrode current collector plate 44a are joined to the positive electrode active material layer non-formed portion 52a and the negative electrode active material layer non-formed portion 62a, respectively.
[0020] As the positive electrode collector 52 constituting the positive electrode sheet 50, a known positive electrode collector used for lithium ion secondary batteries can be used, and examples thereof include sheets or foils made of metals with good conductivity (for example, aluminum, nickel, titanium, stainless steel, etc.). As the positive electrode collector 52, aluminum foil is preferred.
[0021] The size of the positive electrode current collector 52 is not particularly limited and can be appropriately determined according to the battery design. When aluminum foil is used as the positive electrode current collector 52, its thickness is not particularly limited, and is, for example, 5 μm to 35 μm, preferably 7 μm to 20 μm.
[0022] The positive electrode active material layer 54 contains a positive electrode active material and a conductive material. As the positive electrode active material, a known positive electrode active material used in a lithium ion secondary battery can be used. Specifically, for example, as the positive electrode active material, a lithium composite oxide, a lithium transition metal phosphate compound, etc. can be used. There is no particular limitation on the crystal structure of the positive electrode active material, and it can be a layered structure, a spinel structure, an olivine structure, etc.
[0023] As the lithium composite oxide, preferably a lithium transition metal composite oxide containing at least one of Ni, Co, and Mn as a transition metal element. Specific examples thereof include lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.
[0024] It should be noted that in this specification, the so-called "lithium nickel cobalt manganese composite oxide" is a term that includes oxides containing one or more additional elements other than Li, Ni, Co, Mn, and O in addition to oxides containing these elements. Examples of the additional elements include transition metal elements such as Mg, Ca, Al, Ti, V, Cr, Y, Zr, Nb, Mo, Hf, Ta, W, Na, Fe, Zn, and Sn, typical metal elements, and the like. In addition, the additional elements may be semi-metallic elements such as B, C, Si, and P, and non-metallic elements such as S, F, Cl, Br, and I. This is also true for the above-mentioned lithium nickel composite oxides, lithium cobalt composite oxides, lithium manganese composite oxides, lithium nickel manganese composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium iron nickel manganese composite oxides.
[0025] Examples of the lithium transition metal phosphate compound include lithium iron phosphate (LiFePO 4 ), lithium manganese phosphate (LiMnPO 4 ), and lithium manganese iron phosphate.
[0026] These positive electrode active materials may be used alone or in combination of two or more. As the positive electrode active material, lithium nickel cobalt manganese composite oxides are particularly preferred because of their excellent initial resistance characteristics and other properties.
[0027] The positive electrode active material is in a particle shape, and the average particle size (median diameter: D50) of the positive electrode active material is not particularly limited, for example, 0.05 μm or more and 25 μm or less, preferably 1 μm or more and 20 μm or less, and more preferably 3 μm or more and 15 μm or less. In addition, the average particle size (D50) of the positive electrode active material can be obtained, for example, by a laser diffraction scattering method.
[0028] The content of the positive electrode active material in the positive electrode active material layer 54 (i.e., the content of the positive electrode active material relative to the total mass of the positive electrode active material layer 54) is not particularly limited, and is, for example, greater than 80 mass %, preferably greater than 87 mass %, more preferably greater than 90 mass %, further preferably greater than 95 mass %, and most preferably greater than 97 mass %.
[0029] In this embodiment, as the conductive material of the positive electrode active material layer 54, at least carbon nanotubes (CNT) are used, and the proportion of CNT in the conductive material is 80% by mass or more. CNT is usually dispersed in the positive electrode active material layer 54 together with the positive electrode active material in the form of separate particles and / or aggregates. By containing more than 80% by mass of CNT in the conductive material, the initial resistance of the lithium ion secondary battery 100 can be reduced. That is, the initial resistance characteristics of the lithium ion secondary battery can be improved.
[0030] There is no particular limitation on the type of CNT used, for example, single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT), multi-walled carbon nanotubes (MWCNT), etc. can be used. These can be used alone or in combination of two or more. As CNT, MWCNT is preferred. CNT can be manufactured by arc discharge method, laser ablation method, chemical vapor growth method, etc.
[0031] There is no particular limitation on the average length of CNTs. If the average length of CNTs is too long, CNTs will aggregate and dispersibility will decrease, and the effect of uniformly disposing the positive electrode film forming agent in the positive electrode active material layer 54 may be reduced. Therefore, the average length of CNTs is preferably less than 10 μm, more preferably less than 5.0 μm, further preferably less than 3.0 μm, and most preferably less than 1.0 μm. On the other hand, if the average length of CNTs is too short, the number of CNTs per unit mass is excessively reduced, and it may be difficult to form a conductive path between the positive electrode active materials. Therefore, the average length of CNTs is preferably greater than 0.1 μm, more preferably greater than 0.2 μm, and further preferably greater than 0.3 μm.
[0032] The average diameter of CNT is not particularly limited. If the average diameter of CNT is too large, the number of CNTs per unit mass is excessively reduced, and it is likely to be difficult to form a conductive path between the positive electrode active material. Therefore, the average diameter of CNT is preferably less than 50nm, more preferably less than 40nm, and further preferably less than 30nm. On the other hand, if the average diameter of CNT is excessively reduced, the hollow diameter of CNT is excessively reduced, and the impregnation improvement effect of the non-aqueous electrolyte 80 caused by the capillary phenomenon is likely to be reduced. Therefore, the average diameter of CNT is preferably more than 1nm, more preferably more than 5nm, and more preferably more than 8nm.
[0033] Particularly preferably, the average length of the CNTs is 0.3 μm to 1.0 μm, and the average diameter of the CNTs is 8 nm to 30 nm.
[0034] It should be noted that the average length and average diameter of CNTs can be obtained, for example, by taking an electron microscope photograph of CNTs as the average values of the lengths and diameters of more than 100 CNTs. Specifically, for example, a CNT dispersion is diluted and dried to prepare a measurement sample. The sample is observed by a scanning electron microscope (SEM), and the lengths and diameters of more than 100 CNTs are obtained, and the average value is calculated. At this time, in the case of CNT re-agglomeration, the length and diameter of the bundle of condensed CNTs are obtained.
[0035] Examples of conductive materials other than CNTs include carbon materials (for example, carbon black such as acetylene black (AB), graphite, etc.) Among them, carbon black is preferred, and acetylene black is particularly preferred.
[0036] From the viewpoint of particularly high initial resistance characteristics of the lithium ion secondary battery 100 , the ratio of CNTs in the conductive material is preferably 90% by mass or more, and more preferably 100% by mass (ie, the conductive material contains only CNTs).
[0037] The content of the conductive material in the positive electrode active material layer 54 is 0.2 mass % to 1.0 mass %. The significance of this will be described later. The content of the conductive material in the positive electrode active material layer 54 is preferably 0.4 mass % to 1.0 mass %. In this case, the lithium ion secondary battery 100 is a secondary battery in which the resistance increase during long-term storage is highly suppressed.
[0038] The positive electrode active material layer 54 may contain components other than the positive electrode active material, such as trilithium phosphate, a binder, a carbon nanotube dispersant (CNT dispersant), etc. As the binder, for example, polyvinylidene fluoride (PVdF) or the like can be used.
[0039] As a CNT dispersant, for example, a surfactant type dispersant (also called a low molecular weight dispersant), a polymer type dispersant, an inorganic type dispersant, etc. can be used. The CNT dispersant may be any of anionic, cationic, amphoteric or nonionic. Therefore, the CNT dispersant may have at least one functional group selected from anionic groups, cationic groups, and nonionic groups in its molecular structure. In addition, the so-called surfactant refers to an amphiphilic substance having a chemical structure in which a hydrophilic part and a lipophilic part are provided in the molecular structure and they are bonded by a covalent bond.
[0040] As a specific example of CNT dispersant, naphthalenesulfonic acid formalin condensate sodium salt, naphthalenesulfonic acid formalin condensate ammonium salt, methyl naphthalenesulfonic acid formalin condensate sodium salt and other condensation systems of aromatic surfactants can be listed; polycarboxylic acids and salts thereof such as polyacrylic acid and its salts, polymethacrylic acid and its salts; triazine derivative dispersant (preferably containing a triazine derivative dispersant of carbazole or benzimidazole); polyvinyl pyrrolidone (PVP); polymers having polynuclear aromatics such as pyrene and anthracene in the side chain; polynuclear aromatic ammonium derivatives such as pyrene ammonium derivatives (for example, compounds having ammonium bromide groups introduced into pyrene), anthracene ammonium derivatives, etc. These CNT dispersants can be used alone or in combination of two or more. As a CNT dispersant, a CNT dispersant preferably includes a polynuclear aromatic. Specifically, as a CNT dispersant, a polymer having a polynuclear aromatic in the side chain and a polynuclear aromatic ammonium derivative are preferably used.
[0041] The content of trilithium phosphate in the positive electrode active material layer 54 is not particularly limited, but is preferably 1% by mass or more and 15% by mass or less, and more preferably 2% by mass or more and 12% by mass or less. The content of the binder in the positive electrode active material layer 54 is not particularly limited, but is preferably 0.1% by mass or more and 10% by mass or less, and more preferably 0.2% by mass or more and 5% by mass or less, and further preferably 0.3% by mass or more and 2% by mass or less.
[0042] The amount of CNT dispersant can be appropriately determined according to the types of CNT and CNT dispersant. Among them, if the proportion of CNT dispersant is too small, the dispersibility may become insufficient. On the other hand, if the proportion of CNT dispersant is too large, the CNT dispersant is excessively attached to the surface of CNT, which may cause an increase in resistance. In the case where CNT is SWCNT, the amount of CNT dispersant used is, for example, 1 to 400 parts by mass, preferably 20 to 200 parts by mass, relative to 100 parts by mass of CNT. In the case where CNT is MWNT, the amount of CNT dispersant used is, for example, 1 to 100 parts by mass, preferably 4 to 40 parts by mass, relative to 100 parts by mass of CNT.
[0043] The positive electrode active material layer 54 has pores that connect the gaps between the positive electrode active material particles. In the present embodiment, the peak pore diameter of the positive electrode active material layer 54 is 0.50 μm to 0.70 μm. In the present embodiment, the pores of the positive electrode active material layer 54 are small. However, by containing 0.2 mass % to 1.0 mass % of a conductive material of which 80 mass % or more is CNT in the positive electrode active material layer 54, the storage characteristics of the lithium ion secondary battery 100 can be improved.
[0044] By making the content of the conductive material 0.2 mass % or more and making 80 mass % or more of the conductive material CNT, the impregnation of the non-aqueous electrolyte 80 into the positive electrode active material layer 54 is improved by utilizing the capillary phenomenon generated by the CNT located in the pores of the positive electrode active material layer 54. As a result, the positive electrode film forming agent can be supplied to the fine part of the pores of the positive electrode active material layer 54 together with the non-aqueous electrolyte 80. As a result, the positive electrode film forming agent can be uniformly distributed throughout the positive electrode active material layer 54, and a film can be uniformly formed in the positive electrode active material layer 54 when the lithium ion secondary battery 100 is initially charged. Thus, the storage characteristics of the lithium ion secondary battery 100 can be improved. On the other hand, if the content of the conductive material is too much, that is, if it exceeds 1.0 mass %, it is difficult for the non-aqueous electrolyte 80 to flow in the pores due to the excess conductive material. Therefore, by setting the content of the conductive material to 1.0 mass % or less, the positive electrode film forming agent can be uniformly distributed in the positive electrode active material layer 54 , and the above-mentioned effect of improving the storage characteristics of the lithium ion secondary battery 100 can be highly obtained.
[0045] Furthermore, when the conductive material contains 80 mass % or more of CNTs, a good conductive path is formed in the positive electrode active material layer 54 , and the initial resistance of the lithium ion secondary battery 100 can be reduced, thereby improving the initial resistance characteristics.
[0046] The peak pore diameter of the positive electrode active material layer 54 can be measured by mercury intrusion porosimetry. Specifically, the peak pore diameter of the positive electrode active material layer 54 can be measured by a known method using a mercury porosimeter.
[0047] The pores of the positive electrode active material layer 54 are formed by the gaps between the positive electrode active material particles. Therefore, the peak pore diameter of the positive electrode active material layer 54 can be adjusted by controlling the porosity of the positive electrode active material layer 54. When the porosity of the positive electrode active material layer 54 is small, the peak pore diameter of the positive electrode active material layer 54 tends to become smaller. The porosity of the positive electrode active material layer 54 can be adjusted by changing the pressing conditions of the positive electrode active material layer 54 when making the positive electrode 50, controlling the particle diameter of the positive electrode active material particles, etc. Alternatively, by configuring a conductive material in the gaps between the positive electrode active material particles, the pore diameter can be reduced. Therefore, the peak pore diameter of the positive electrode active material layer 54 can also be controlled by the amount of conductive material used.
[0048] The porosity of the positive electrode active material layer 54 is preferably 15% to 40% by volume, more preferably 15% to 30% by volume, and further preferably 15% to 25% by volume. The porosity of the positive electrode active material layer 54 can be measured by mercury intrusion porosimetry. Specifically, the porosity of the positive electrode active material layer 54 can be measured by a known method using a mercury porosimeter.
[0049] The thickness of the positive electrode active material layer 54 is not particularly limited, and is, for example, 10 μm or more and 400 μm or less, and preferably 20 μm or more and 300 μm or less.
[0050] The density of the positive electrode active material layer 54 is not particularly limited, but is, for example, 2.00 g / cm 3 ~4.00g / cm 3 From the viewpoint of high volume energy density, the density of the positive electrode active material layer 54 is preferably 3.00 g / cm 3 ~4.00g / cm 3 , more preferably 3.40 g / cm 3 ~4.00g / cm 3 , more preferably 3.50 g / cm 3 ~4.00g / cm 3 , particularly preferably 3.60 g / cm 3 ~4.00g / cm 3 .
[0051] The positive electrode sheet 50 may include an insulating layer (not shown) at the boundary between the positive electrode active material layer non-formed portion 52a and the positive electrode active material layer 54. The insulating layer includes, for example, ceramic particles.
[0052] A known negative electrode collector used in lithium ion secondary batteries can be used as the negative electrode collector 62 constituting the negative electrode sheet 60, and examples thereof include sheets or foils made of metals with good conductivity (such as copper, nickel, titanium, stainless steel, etc.). The negative electrode collector 62 is preferably copper foil.
[0053] The size of the negative electrode current collector 62 is not particularly limited and can be appropriately determined according to the battery design. When copper foil is used as the negative electrode current collector 62, its thickness is not particularly limited, and is, for example, 5 μm to 35 μm, preferably 6 μm to 20 μm.
[0054] The negative electrode active material layer 64 contains a negative electrode active material. As the negative electrode active material, for example, carbon materials such as graphite, hard carbon, and soft carbon can be used. The graphite can be natural graphite or artificial graphite, and the graphite can be amorphous carbon-coated graphite in a form coated with an amorphous carbon material.
[0055] The average particle size (median diameter: D50) of the negative electrode active material is not particularly limited, and is, for example, 0.1 μm or more and 50 μm or less, preferably 1 μm or more and 25 μm or less, and more preferably 5 μm or more and 20 μm or less. Furthermore, the average particle size (D50) of the negative electrode active material can be obtained, for example, by laser diffraction scattering.
[0056] The negative electrode active material layer 64 may contain components other than the active material, such as a binder, a thickener, etc. As the binder, for example, styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), etc. can be used. As the thickener, for example, carboxymethyl cellulose (CMC) can be used.
[0057] The content of the negative electrode active material in the negative electrode active material layer 64 is preferably 90% by mass or more, more preferably 95% by mass or more and 99% by mass or less. The content of the binder in the negative electrode active material layer 64 is preferably 0.1% by mass or more and 8% by mass or less, more preferably 0.5% by mass or more and 3% by mass or less. The content of the thickener in the negative electrode active material layer 64 is preferably 0.3% by mass or more and 3% by mass or less, more preferably 0.5% by mass or more and 2% by mass or less.
[0058] The thickness of the negative electrode active material layer 64 is not particularly limited, and is, for example, 10 μm or more and 400 μm or less, and preferably 20 μm or more and 300 μm or less.
[0059] As the separator 70, for example, a porous sheet (film) made of a resin such as polyethylene (PE), polypropylene (PP), polyester, cellulose, polyamide, etc. can be cited. The porous sheet can be a single-layer structure or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer). A heat-resistant layer (HRL) containing ceramic particles or the like can be provided on the surface of the separator 70.
[0060] The thickness of the separator 70 is not particularly limited, and is, for example, 5 μm to 50 μm, preferably 10 μm to 30 μm. The air permeability of the separator 70 measured by the Gray test is not particularly limited, and is preferably 350 sec / 100 cc or less.
[0061] The nonaqueous electrolyte 80 contains a nonaqueous solvent, an electrolyte salt (in other words, a supporting salt), and a positive electrode film-forming agent.
[0062] As non-aqueous solvent, various organic solvents such as carbonates, ethers, esters, nitriles, sulfones, lactones used in the electrolyte of general lithium ion secondary batteries can be used without particular limitation. Among them, carbonates and esters are preferred. As specific examples thereof, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), methyl acetate, methyl propionate, etc. can be illustrated. Such non-aqueous solvent can be used alone or in combination of two or more. Non-aqueous solvent contains only carbonates, for example. Non-aqueous solvent contains only carbonates, for example, and esters.
[0063] As the electrolyte salt, for example, lithium salts such as LiPF6, LiBF4, and lithium bis(fluorosulfonyl)imide (LiFSI) (preferably LiPF6) can be preferably used. The concentration of the electrolyte salt in the non-aqueous electrolyte 80 is preferably 0.7 mol / L or more and 1.3 mol / L or less.
[0064] The positive electrode film forming agent is a component that forms a film on the positive electrode active material layer 54 (especially the surface of the positive electrode active material particles) when the lithium ion secondary battery 100 is initially charged, and is also called a positive electrode additive. As the positive electrode film forming agent, at least one selected from lithium difluorophosphate (LiPO2F2) and lithium fluorosulfate (LiSO3F) can be preferably used. By using them, the storage characteristics of the lithium ion secondary battery 100 can be made particularly high.
[0065] The concentration of the positive electrode film forming agent in the non-aqueous electrolyte 80 is not particularly limited, and is, for example, 0.05 mass % to 2.0 mass %, preferably 0.1 mass % to 1.8 mass %, and more preferably 0.3 mass % to 1.5 mass %.
[0066] Furthermore, the above-mentioned non-aqueous electrolyte 80 may contain components other than the above-mentioned components, such as negative electrode film forming agents such as vinylene carbonate (VC) and oxalic acid complex; gas generating agents such as biphenyl (BP) and cyclohexylbenzene (CHB); and various additives such as thickeners, as long as the effects of the present invention are not significantly impaired.
[0067] In the lithium ion secondary battery 100, although the pores of the positive electrode active material layer are small, the capacity degradation during long-term storage is suppressed. In addition, in the lithium ion secondary battery 100, the resistance increase during long-term storage is well suppressed. Therefore, the storage characteristics of the lithium ion secondary battery 100 are excellent. Furthermore, the output characteristics of the lithium ion secondary battery 100 are also excellent. Furthermore, the reaction distribution in the positive electrode 50 is easy to become uniform, thereby making it difficult for lithium to precipitate on the surface of the negative electrode 60, and the capacity degradation is also difficult.
[0068] The lithium ion secondary battery 100 can be used in various applications. As preferred applications, a driving power source mounted in vehicles such as electric vehicles (BEV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV) can be listed. In addition, the lithium ion secondary battery 100 can be used as a storage battery for a small power storage device, etc. A particularly preferred application of the lithium ion secondary battery 100 is a driving power source for BEV. The lithium ion secondary battery 100 can also be used in the form of a battery pack typically formed by connecting a plurality of batteries in series and / or in parallel.
[0069] As an example, a square lithium-ion secondary battery 100 having a flat wound electrode body 20 is described above. However, the lithium-ion secondary battery can also be configured as a lithium-ion secondary battery having a stacked electrode body (i.e., an electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked). In addition, the lithium-ion secondary battery can also be configured as a cylindrical lithium-ion secondary battery, a stacked shell lithium-ion secondary battery, etc.
[0070] The secondary battery according to the present embodiment can be configured as a nonaqueous electrolyte secondary battery other than a lithium ion secondary battery according to a known method.
[0071] Hereinafter, examples related to the present invention will be described in detail, but the present invention is not intended to be limited to the embodiments shown in these examples.
[0072] [Examples 1 to 3 and Comparative Examples 1 to 8]
[0073] LiNi as the positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O2, conductive material and PVdF as a binder are mixed in a mass ratio of active material: conductive material: PVdF = 99.5-x: x: 0.5. In addition, MWCNT (average diameter 13nm, average length 0.5μm) and acetylene black are used as conductive materials. MWCNT is used in the form of a dispersion containing pyrene ammonium salt as a CNT dispersant. The x1 shown in Table 1 is the mass ratio of MWCNT, x2 is the mass ratio of AB, and the sum of x1 and x2 is the mass ratio x of the conductive material.
[0074] An appropriate amount of N-methyl-2-pyrrolidone was added to the obtained mixture to prepare a positive electrode slurry. The positive electrode slurry was applied to both sides of a 13 μm thick aluminum foil as a positive electrode current collector. At this time, a positive electrode slurry uncoated portion was set on the aluminum foil as a lead connection portion. In addition, the coating amount of the positive electrode slurry was adjusted so that the unit area mass of the formed positive electrode active material layer became 45 mg / cm 2 (Total of both sides).
[0075] The coated slurry is dried to form a positive electrode active material layer. The obtained sheet is pressed using a roller, and the porosity of the positive electrode active material layer is adjusted to 21 volume % while the positive electrode active material layer is densified. In addition, the porosity is measured using a commercially available mercury porosimeter. It is cut into a specified size to obtain a positive electrode with a positive electrode active material layer formed on both sides of the positive electrode collector.
[0076] In terms of the mass ratio of solid components, the dispersion of graphite, sodium salt of carboxymethyl cellulose (CMC-Na) and styrene butadiene rubber (SBR) as carbon-based negative electrode active materials is mixed at a ratio of graphite: CMC-Na: CMC = 98:1:1. Furthermore, an appropriate amount of ion exchange water is added to prepare a negative electrode slurry. The negative electrode slurry is applied on both sides of a copper foil with a thickness of 8 μm as a negative electrode collector. At this time, a negative electrode slurry uncoated portion is set on the copper foil as a lead connection portion.
[0077] The applied paste was dried to form a negative electrode active material layer. The obtained sheet was pressed with a roller and then cut into a predetermined size to obtain a negative electrode having negative electrode active material layers formed on both sides of the negative electrode current collector. The packing density of the negative electrode active material layer was 1.50 g / cm 3 .
[0078] Leads were attached to the positive electrode and negative electrode prepared above, respectively, and a single-layer polypropylene separator was prepared. The positive electrode and the negative electrode were alternately stacked one by one through the separator to prepare a stacked electrode body.
[0079] A mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:40:30 is prepared. In the mixed solvent, vinylene carbonate is dissolved at a concentration of 1 mass %, lithium bis(oxalate)borate is dissolved at a concentration of 0.8 mass %, lithium fluorosulfate as a positive electrode film forming agent is dissolved at a concentration of 1.5 mass %, and LiPF6 as a supporting salt is dissolved at a concentration of 1.15 mol / L. However, in Comparative Example 8, no positive electrode film forming agent is added. As described above, a non-aqueous electrolyte is obtained.
[0080] The stacked electrode body and the nonaqueous electrolyte prepared above were placed in a rectangular battery case and sealed to obtain a rectangular lithium ion secondary battery for evaluation. The injection amount of the nonaqueous electrolyte was 2.05 g / Ah.
[0081] <Peak pore diameter measurement>
[0082] The peak pore diameter (μm) of the positive electrode active material layer of the positive electrode prepared as described above was determined using a commercially available mercury porosimeter (“AutoPore V9620” manufactured by Micromeritics Corporation).
[0083] <PC impregnation speed evaluation>
[0084] On the positive electrode active material layer of the positive electrode prepared above, 3 μL of propylene carbonate (PC) solvent was dripped using a micropipette. By visual inspection, the time (seconds) from the time of dripping to the time when the PC solvent was completely absorbed into the positive electrode active material layer was measured. The measurement was performed 20 times, and the average value was used as the PC impregnation time. The results are shown in Table 1. Furthermore, the shorter the PC impregnation time, the faster the PC impregnation speed, and the easier it is for the non-aqueous electrolyte to be impregnated in the positive electrode active material layer.
[0085] <Initial resistance characteristics evaluation - output resistance measurement>
[0086] Each evaluation lithium-ion secondary battery was charged by constant current constant voltage (CC-CV) and adjusted to SOC (State of charge) 50%, and then placed in an environment of 25°C. The battery was charged for 10 seconds at a current value of 4C, and the voltage increase ΔV at this time was obtained. The output resistance value (initial output resistance) of each evaluation secondary battery was calculated using the voltage increase ΔV and the current value. The results are shown in Table 1.
[0087] <Evaluation of storage characteristics>
[0088] Each evaluation lithium ion secondary battery was placed in an environment of 25°C and charged to 4.25 V by CC-CV charging (0.01C cut-off) to adjust the SOC to 100%. Then, CC-CV discharge (0.01C cut-off) was performed at a current value of 1 / 3C to 3 V. The discharge capacity at this time was measured and set as the initial capacity.
[0089] Next, each evaluation lithium ion secondary battery was adjusted to SOC 95% and stored in a thermostatic chamber at 60°C for 45 days. Then, the discharge capacity was measured in the same manner as the initial capacity. The capacity retention rate (%) was calculated by (discharge capacity after storage / initial capacity)×100. The results are shown in Table 1.
[0090] In addition, the output resistance value of each evaluation lithium ion secondary battery after storage was measured by the same method as above. As the resistance increase ratio, the value of (output resistance after storage / initial output resistance) was calculated. The results are shown in Table 1. In addition, in Comparative Example 7, since the initial output resistance was high, the storage characteristics were not evaluated.
[0091] <Measurement of the residual concentration of the positive electrode film forming agent>
[0092] Each evaluation lithium-ion secondary battery was placed in an environment of 25°C, charged by CC-CV, charged to 4.25V, and adjusted to SOC100%. Then, CC-CV discharge was performed with a current value of 1 / 3C until 3V. Then, each evaluation lithium-ion secondary battery was disassembled and the non-aqueous electrolyte was recovered. The residual concentration of the positive electrode film forming agent in the non-aqueous electrolyte was determined using a desktop NMR spectrometer "X-Pulse" (with an automatic sampler "X-Auto") manufactured by Oxford Instruments. The results are shown in Table 1.
[0093] [Table 1]
[0094]
[0095] From the results of Comparative Examples 2 to 6, it can be seen that the larger the peak pore diameter of the positive electrode active material layer, the shorter the PC impregnation time, that is, the impregnation of the non-aqueous electrolyte increases. Among them, Comparative Examples 2 to 5 are examples in which only AB is used as the conductive material. In Comparative Examples 2 to 5, it can be seen that the smaller the amount of AB, the larger the peak pore diameter, the higher the impregnation of the non-aqueous electrolyte, and the positive electrode film forming agent is consumed in large quantities by the film formation. In addition, in Comparative Examples 2 to 5, it can be seen that the smaller the amount of AB, the worse the output characteristics and storage characteristics.
[0096] On the other hand, Examples 1 to 3 and Comparative Example 1 are examples of the case where only CNTs are used for conductive materials. As can be seen from the comparison with Comparative Examples 2 to 6, when CNTs are used for conductive materials, a different tendency is obtained from the case where AB is used. Specifically, it can be seen that when the CNT content is 0.2% by mass to 1.0% by mass, the residual concentration of the positive electrode film forming agent is specifically reduced, the output resistance is reduced, and the storage characteristics are improved. It is believed that this is because, by using CNTs, the positive electrode film forming agent can penetrate into the fine parts of the pores of the positive electrode active material layer, and the film can be uniformly formed in the positive electrode active material layer.
[0097] In addition, from the comparison between Comparative Example 7 and Examples 1 to 3, it can be seen that the reduction in output resistance and the improvement in storage characteristics can be achieved only when the ratio of CNT to the conductive material is high.
[0098] As described above, according to the nonaqueous electrolyte secondary battery disclosed herein, it is possible to provide a nonaqueous electrolyte secondary battery having excellent output characteristics and storage characteristics despite having small pores in the positive electrode active material layer.
[0099] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.
[0100] That is, the nonaqueous electrolyte secondary battery disclosed herein is the following items [1] to [6].
[0101] [1] A non-aqueous electrolyte secondary battery, comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein the positive electrode comprises a positive electrode collector and a positive electrode active material layer supported on the positive electrode collector, the positive electrode active material layer comprises a positive electrode active material and a conductive material, the peak pore diameter of the positive electrode active material layer is 0.50 μm to 0.70 μm, the content of the conductive material in the positive electrode active material layer is 0.2 mass % to 1.0 mass %, more than 80 mass % of the conductive material is carbon nanotubes, and the non-aqueous electrolyte comprises a non-aqueous solvent, an electrolyte salt, and a positive electrode film forming agent.
[0102] [2] The nonaqueous electrolyte secondary battery according to item [1], wherein the conductive material contains only the carbon nanotubes.
[0103] [3] The nonaqueous electrolyte secondary battery according to item [1] or [2], wherein the positive electrode film-forming agent is at least one selected from lithium difluorophosphate and lithium fluorosulfate.
[0104] [4] The nonaqueous electrolyte secondary battery according to any one of items [1] to [3], wherein the content of the conductive material in the positive electrode active material layer is 0.4 mass % to 1.0 mass %.
[0105] [5] The nonaqueous electrolyte secondary battery according to any one of items [1] to [4], wherein the carbon nanotubes have an average length of 0.3 μm to 1.0 μm and an average diameter of 8 nm to 30 nm.
[0106] [6] The nonaqueous electrolyte secondary battery according to any one of items [1] to [5], which is used as a vehicle driving power source for an electric vehicle.
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein: The positive electrode includes a positive electrode collector and a positive electrode active material layer supported on the positive electrode collector, the positive electrode active material layer contains a positive electrode active material and a conductive material, the peak pore diameter of the positive electrode active material layer is 0.50μm~0.70μm, the content of the conductive material in the positive electrode active material layer is 0.2% by mass~1.0% by mass, more than 80% by mass of the conductive material is carbon nanotubes, and the non-aqueous electrolyte contains a non-aqueous solvent, an electrolyte salt, and a positive electrode film forming agent.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The conductive material only includes the carbon nanotubes.
3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The positive electrode film forming agent is at least one selected from lithium difluorophosphate and lithium fluorosulfate.
4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The content of the conductive material in the positive electrode active material layer is 0.4 mass % to 1.0 mass %.
5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The carbon nanotubes have an average length of 0.3 μm to 1.0 μm and an average diameter of 8 nm to 30 nm. 6 . The nonaqueous electrolyte secondary battery according to claim 1 , which is used as a vehicle driving power source of an electric vehicle.
Citation Information
Patent Citations
Positive electrode material for lithium ion secondary battery, positive electrode for lithium ion secondary battery, and lithium ion secondary battery
JP2015069822A
Nonaqueous electrolyte secondary battery
WO2021186949A1
Non-aqueous electrolyte secondary battery
WO2023054308A1